Halogen regulation triggers structural transformation from centrosymmetric to noncentrosymmetric switches in tin phosphate halides Sn2PO4X (X = F, Cl). Issue 18 (27th July 2022) - Zheng, Ting; Wang, Qiang; Ren, JinXuan; Cao, Liling; Huang, Ling; Gao, Daojiang; Bi, Jian; Zou, Guohong
Abstract : A tin phosphate halide, centrosymmetric Sn2 PO4 F, was successfully transformed into noncentrosymmetric Sn2 PO4 Cl with excellent comprehensive performance by the substitution of F − with Cl − . Abstract : Generally, phosphates are employed to design ultraviolet nonlinear optical crystals. However, phosphates always suffer from too small birefringence to effectively achieve phase matching. Herein, the Sn 2+ cation with a stereochemically active lone pair was introduced into a phosphate as a birefringence-active unit, and two tin phosphate halides Sn2 PO4 X (X = F, Cl) were successfully synthesized. Interestingly, the different coordination environments of the Sn-polyhedron caused by the partial substitution of halide ions (F − /Cl − ) with different ionic radii for the oxygen ligands lead to structural transformation from centrosymmetric (CS) Sn2 PO4 F to noncentrosymmetric (NCS) Sn2 PO4 Cl. Thus, Sn2 PO4 X (X = F, Cl) were characterized by enlarged birefringence, and Sn2 PO4 Cl is type I phase-matchable with a moderate SHG response, and is a potential ultraviolet nonlinear optical material. Furthermore, both phosphates show wide band gaps. Theoretical analysis confirmed that their excellent optical properties result from the synergistic effect of the [SnOX] (X = F, Cl) polyhedra with stereochemically active lone pairs and the [PO4 ] 3− tetrahedron.